Spatial dependence of the growth of polycyclic aromatic compounds in an ethylene counterflow flame. (August 2019) - Wang, Qi; Elvati, Paolo; Kim, Doohyun; Johansson, K. Olof; Schrader, Paul E.; Michelsen, Hope A.; Violi, Angela
Abstract: The complex environments that characterize combustion systems can influence the distribution of gas-phase species, the relative importance of various growth mechanisms and the chemical and physical characteristics of the soot precursors generated. In order to provide molecular insights on the effect of combustion environments on the formation of gas-phase species, in this paper, we study the temporal and spatial dependence of soot precursors growth mechanisms in an ethylene/oxygen/argon counterflow diffusion flame. As computational tools of investigation, we included fluid dynamics simulations and stochastic discrete modeling. Results show the relative importance of various reaction pathways in flame, with the hydrogen-abstraction-acetylene-addition mechanism contributing to the formation of pure hydrocarbons near the stagnation plane, and oxygen chemistry prevailing near the maximum temperature region, where the concentration of atomic oxygen reaches its peak and phenols, ethers and furan-embedded species are formed. The computational results show excellent agreement with measurements obtained using aerosol mass spectrometry coupled with vacuum-ultraviolet photoionization. Knowledge acquired in this study can be used to predict the type of compounds formed in various locations of the flame and eventually provide insights on the environmental parameters that influence the growth of soot precursors. Additionally, the results reported in this paper highlight the importance of modeling counterflow flames in two or three dimensions to capture the spatial dependence of growth mechanisms of soot precursors. Graphical abstract: Image 1